2022
DOI: 10.1182/blood.2021014804
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning intensity and peritransplant flow cytometric MRD dynamics in adult AML

Abstract: In acute myeloid leukemia (AML), measurable residual disease (MRD) before or after allogeneic hematopoietic cell transplantation (HCT) is an established, independent indicator of poor outcome. To address how peri-HCT MRD dynamics could refine risk assessment across different conditioning intensities, we analyzed 810 adults transplanted in remission after myeloablative conditioning (MAC; n=515) or non-MAC (n=295) who underwent multiparameter flow cytometry-based MRD testing before and 20-40 days after allograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 26 publications
3
38
1
Order By: Relevance
“…Best responses were assessed after 1–2 cycles of induction chemotherapy and defined according to standard criteria [ 14 ]. Measurable residual disease (MRD) was assessed by multiparametric flow cytometry (MFC) as described, with any level of residual disease considered MRD pos [ 15 , 16 , 17 , 18 ]. Relapse after study treatment was defined by standard morphologic criteria [ 14 ] or any disease recurrence at the MRD or cytogenetic level if leading to therapeutic intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Best responses were assessed after 1–2 cycles of induction chemotherapy and defined according to standard criteria [ 14 ]. Measurable residual disease (MRD) was assessed by multiparametric flow cytometry (MFC) as described, with any level of residual disease considered MRD pos [ 15 , 16 , 17 , 18 ]. Relapse after study treatment was defined by standard morphologic criteria [ 14 ] or any disease recurrence at the MRD or cytogenetic level if leading to therapeutic intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Data from 440 of the 506 patients in the final study cohort have been partially reported. [22][23][24][25][26][27][28][29][30][31][32] The HCT-specific comorbidity index (HCT-CI) was calculated as described. 33 Related or unrelated donors were selected by high resolution HLA-typing.…”
Section: Study Cohortmentioning
confidence: 99%
“…2,34 Cytogenetically normal AML was considered in patients with a normal karyotype regardless of how many metaphases were available for analysis. [30][31][32]35 Since molecular data at time of diagnosis were lacking in many patients, only cytogenetic risk could be used to classify patients.…”
Section: Classification Of Disease Risk and Treatment Responsementioning
confidence: 99%
See 2 more Smart Citations